Hadith In Historical Review : Cross-flow Perspective - Liadi, Muslim; Santika, Mira; Fitriyadi, Muhammad (International Journal of Applied and Scientific Research, 2024)
The writing of hadith in this cross-stream perspective historical review is the result of literature research, which is a method obtained by collecting data and information sourced from literature. The process involves a series of procedures for collecting data from library sources which are then processed from various stages of analysis, and ultimately produce research findings. The characteristics of the Hadith of the Prophet's period of Revelation revealed by Allah were explained by the Prophet through his words, deeds, and taqrir. Characteristics of the Hadith period Muslim companions can directly obtain hadith from the Prophet as a source of hadith. The characteristics of hadiths from the tabi period were collected and discarded through talaqqi with the companions then they recorded what was gained from the meeting. Characteristics of Hadith period Tabi' at-Tabi'in Group existing hadiths according to the field of discussion. Three elements must be met in order to be called a hadith narrative. The three elements are (1) the activity of receiving hadith (al-tahammul), (2) the re-delivery of hadith, and (al-ada') (3) the mention of a series of narrators at the time of the hadith (al-isnad). The history of the development of hadith is a period or period that has been passed by hadith since the moment of its birth and grew in the introduction, appreciation, and practice of the ummah from generation to generation.